2014
DOI: 10.1371/journal.pone.0099526
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic Toll-Like Receptor 3 Is Associated with Ischemic Preconditioning- Induced Protection against Brain Ischemia in Rodents

Abstract: BackgroundCerebral ischemic preconditioning (IPC) protects brain against ischemic injury. Activation of Toll-like receptor 3 (TLR3) signaling can induce neuroprotective mediators, but whether astrocytic TLR3 signaling is involved in IPC-induced ischemic tolerance is not known.MethodsIPC was modeled in mice with three brief episodes of bilateral carotid occlusion. In vitro, IPC was modeled in astrocytes by 1-h oxygen-glucose deprivation (OGD). Injury and components of the TLR3 signaling pathway were measured af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 50 publications
4
40
0
Order By: Relevance
“…The large overlap between molecular pathways activated in response to LPS and ischemia is, in part, responsible for the phenomenon of crosstolerance (discussed previously), suggesting that IPC may modulate microglia/astrocyte interplay, with both cells playing important roles in conferring IPC-mediated neuroprotection. Astrocytes express TLR4 [108], a critical component in IPC-mediated neuroprotection [11,12]. Activation of astrocytic TLR4 results in activation of nuclear factor kB and signal transducer and activator of transcription 3 in astrocytes [109], and downstream of this pathway is growth-associated protein (GAP)43, which is a protein kinase C-activated phosphoprotein implicated in axonal plasticity and regeneration [109].…”
Section: Astrocytesmentioning
confidence: 99%
“…The large overlap between molecular pathways activated in response to LPS and ischemia is, in part, responsible for the phenomenon of crosstolerance (discussed previously), suggesting that IPC may modulate microglia/astrocyte interplay, with both cells playing important roles in conferring IPC-mediated neuroprotection. Astrocytes express TLR4 [108], a critical component in IPC-mediated neuroprotection [11,12]. Activation of astrocytic TLR4 results in activation of nuclear factor kB and signal transducer and activator of transcription 3 in astrocytes [109], and downstream of this pathway is growth-associated protein (GAP)43, which is a protein kinase C-activated phosphoprotein implicated in axonal plasticity and regeneration [109].…”
Section: Astrocytesmentioning
confidence: 99%
“…Notwithstanding, the role of TLR3 in the pineal gland may be more complex. Recent studies carried out on mice (Pan et al, 2014) showed that astrocytic TLR3 signaling plays an important role in suppression of the post-ischaemic inflammatory response and thereby protects against ischaemic damage. Therefore, the expression of TLR3 in the pineal gland may be involved in the protection of this tissue against strong inflammatory stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…25 Recently, in an animal study of Pan et al ischemic preconditioning reduced brain injury and the systemic inflammatory response, reported by decreased IL-6 levels. 26 Altogether, it could be concluded that reduced IL-6 levels may be an important consequence of ischemic conditioning in the ischemic kidney. Several molecular pathways are implicated in remote ischemic condition models which predominantly implicates systemic multifactorial anti-inflammatory, neuronal, and humoral signaling pathways.…”
Section: 10mentioning
confidence: 98%